3
$\begingroup$

if $x,y,z$ are positive real numbers and $x+y+z=1$ Prove:$$\sum_{cyc} \frac{\sqrt{xy}}{\sqrt{xy+z}}\le\frac{3}{2}$$ where $\sum_{cyc}$ denotes sums over cyclic permutations of the symbols $x,y,z$.

Additional info:I'm looking for solutions and hint that using Cauchy-Schwarz and AM-GM because I have background in them.

Things I have done so far: Using AM-GM $$xy+z \ge 2$$ $$\sqrt{xy+z} \ge \sqrt2$$ So manipulating this leads to $$\sum_{cyc}\frac{\sqrt{xy}}{\sqrt{xy+z}} \le \sum_{cyc}\frac{\sqrt{xy}}{\sqrt2}$$

I stuck here.I'm thinking about applying Cauchy-Schwartz.Also I have not used the assumption $x+y+z=1$.Any hint is appreciated.

$\endgroup$
  • $\begingroup$ It's not true that $xy+z\ge 2$. $\endgroup$ – Quang Hoang Aug 27 '14 at 8:25
  • $\begingroup$ @idm $$\sum_{cyc} \frac{\sqrt{xy}}{\sqrt{xy+z}}=\frac{\sqrt{xy}}{\sqrt{xy+z}} +\frac{\sqrt{yz}}{\sqrt{yz+x}} +\frac{\sqrt{zx}}{\sqrt{zx+y}}$$ $\endgroup$ – user2838619 Aug 27 '14 at 8:27
  • $\begingroup$ @QuangHoang,you are right. i made a mistake the by thinking it is $xyz=1$. $\endgroup$ – user2838619 Aug 27 '14 at 8:30
7
$\begingroup$

$$\sum_{cyc} \frac{\sqrt{xy}}{\sqrt{xy+z}}\le\frac{3}{2} $$ $$ \sum_{cyc} \frac{\sqrt{xy}}{\sqrt{xy+z}} = \sum_{cyc} \frac{\sqrt{xy}}{\sqrt{xy+1-x-y}} = \sum_{cyc} \frac{\sqrt{xy}}{\sqrt{(1-x)(1-z)}} = \sum_{cyc} \frac{\sqrt{xy}}{\sqrt{(y+z)(x+z)}} $$ And now, by AM-GM $$ \sum_{cyc} \frac{\sqrt{xy}}{\sqrt{(y+z)(x+z)}} \le \sum_{cyc} \frac{x}{2(x+z)}+\frac{y}{2(y+z)} = \frac{x}{2(x+z)}+\frac{y}{2(y+z)} + \frac{y}{2(y+x)}+\frac{z}{2(z+x)}+ \frac{z}{2(z+x)}+\frac{x}{2(x+y)} = \frac{3}{2} \Box $$

$\endgroup$
0
$\begingroup$

HINT 1: $$\sum_{cyc} \frac{\sqrt{xy}}{\sqrt{xy+z}}\le \sqrt{\left(\sum_{cyc}xy\right)\left(\sum_{cyc}\frac1{xy+z}\right)}$$


HINT 2: $$\frac{\sqrt{xy}}{\sqrt{xy+z}}=\frac{1}{\sqrt{1+\frac{z}{xy}}}$$ Let $a=z/xy,b=x/yz,a=y/zx$, now $abc=1$, so $(1+a)\ge a$ So $$\sum_{cyc}\frac1{\sqrt{1+a}}\le\sum_{cyc}\frac1{\sqrt{a}}=\sum_{cyc}\frac{\sqrt{xy}}{\sqrt z}$$

$\endgroup$
  • $\begingroup$ It can never work to use $1+a\geq a$ because we expect an equality for $a=1$, not $a=0$. $\endgroup$ – Bart Michels Aug 28 '14 at 18:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.